2022
DOI: 10.3389/fendo.2022.1002320
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of prolactin and the role of dopamine agonists: A review

Abstract: Prolactin is a polypeptide hormone that is well known for its role in reproductive physiology. Recent studies highlight its role in neurohormonal appetite regulation and metabolism. Elevated prolactin levels are widely associated with worsening metabolic disease, but it appears that low prolactin levels could also be metabolically unfavorable. This review discusses the pathophysiology of prolactin related metabolic changes, and the less commonly recognized effects of prolactin on adipose tissue, pancreas, live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 114 publications
1
15
1
3
Order By: Relevance
“…According to the Endocrine society guidelines, the treatment response of a prolactinoma is defined as the normalization of prolactin levels on maximally tolerated doses of dopamine agonists and a reduction of 50% in the size of the prolactinoma [ 3 ]. However, when there is a lack of response, it could be due to cabergoline-resistant tumors resulting from a decreased number of dopamine [ 2 ] receptors, a CSF leak, or intolerance to or poor compliance with cabergoline. In addition, it is suggested that some patients with cabergoline resistance have higher prolactin levels at diagnosis, and require longer periods for normalization [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Endocrine society guidelines, the treatment response of a prolactinoma is defined as the normalization of prolactin levels on maximally tolerated doses of dopamine agonists and a reduction of 50% in the size of the prolactinoma [ 3 ]. However, when there is a lack of response, it could be due to cabergoline-resistant tumors resulting from a decreased number of dopamine [ 2 ] receptors, a CSF leak, or intolerance to or poor compliance with cabergoline. In addition, it is suggested that some patients with cabergoline resistance have higher prolactin levels at diagnosis, and require longer periods for normalization [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prolactinoma is the most common type of hormone-secreting pituitary tumor and accounts for about 40% of all pituitary adenomas. The prevalence of clinically apparent prolactinomas ranges from 6–10 per 100,000 to 50 per 100,000, according to different studies [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…DA levels in this key area for hormonal regulation could regulate the observed differences between males and females on consumption of sweets. For example, DA modulates prolactin (PRL) synthesis and secretion (Fernandez-Ruiz et al 1989 ; Mena et al 1989 ; Kochman et al 1993 ), and DA receptor agonists, via PRL, can regulate blood glucose content (Kirsch et al 2022 ; Chien et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Один из них расположен проксимально и отвечает за направление специфичной для гипофиза экспрессии, другой -дистально и отвечает за внегипофизарную экспрессию пролактина [1]. Пролактин обеспечивает аутокринную и паракринную обратную связь на лактотрофные клетки гипофиза [3,4]. К факторам, стимулирующим выработку пролактина, относят тиреотропин-рилизинг гормон, эстрогены (при беременности) и антагонисты дофамина (нейролептики).…”
unclassified
“…Примечание. Статистически значимые отличия от: 1 -уровня до лечения в пределах одной группы, 2 -от уровня соответствующего показателя в группе с прогрессированием процесса, 3 -от уровня соответствующего показателя в группе со стабилизацией процесса, 4 -от уровня соответствующего показателя в группе с частичным ответом, 5…”
unclassified